IL-34 Actions on FOXP3+ Tregs and CD14+ Monocytes Control Human Graft Rejection - Bézie, Séverine; Freuchet, Antoine; Sérazin, Céline; Salama, Apolline; Vimond, Nadège; Anegon, Ignacio; Guillonneau, Carole (Frontiers in Immunology, 2020)
Cytokines are major players regulating immune responses towards inflammatory vs. tolerogenic results. In organ and bone marrow transplantation new reagents are needed to inhibit tissue destructive mechanisms and eventually induce immune tolerance without overall immunosuppression. IL-34 is a cytokine with no significant homology with any other cytokine but that acts preferentially through CSF-1R, as CSF-1 does, and through PTPz. Although IL-34 and CSF-1 share actions, a detailed analysis of their effects on immune cells needs further research. We previously showed that both CD4+ and CD8+ FOXP3+ Tregs suppress effector T cells through production of IL-34, but not CSF-1, and that this action was mediated through antigen-presenting cells. We show here by single-cell RNAseq and cytofluorimetry that different subsets of human monocytes express different levels of CSF-1R and PTPz and that both CD4+ and CD8+ FOXP3+ Tregs express higher levels of CSF-1R than T conventional cells. The effects of IL-34 differ in the survival of these different subpopulations of monocytes and RNAseq analysis showed different genes expressed between IL-34, CSF-1, M0, M1 and also M2 macrophages. Acute graft-vs-host disease (aGVHD) in immunodeficient NSG mice injected with human PBMCs was decreased when treated with IL-34 in combination with an anti-CD45RC mAb that depletes T conventional cells. When IL-34-differentiated monocytes were used to expand Tregs in vitro, both CD4+ and CD8+ FOXP3+ Tregs were highly enriched and this effect was superior to the one obtained with CSF-1. Human CD8+ Tregs expanded in vitro with IL-34-differentiated allogeneic monocytes suppressed human immune responses using NSG mice using both the humanized aGVHD model and a model of human allogeneic skin rejection by hPBMCs. Overall, we show that IL-34 induced the differentiation of human monocytes with a particular transcriptional profile and these cells favor the development of potent suppressor FOXP3+ Tregs.